Modern practice of internal medicine with emergency conditions. Management of the patient with chronic cough : guidelines for students and interns - Бабак, Олег Якович; Зайченко, Ольга Євгенівна; Зелена, Ірина Іванівна; Железнякова, Наталя Мерабівна; Гопцій, Олена Вікторівна; Андрєєва, Анастасія Олександрівна; Ситник, Ксенія Олександрівна; Просоленко, Костянтин Олександрович; Лапшина, Катерина Аркадіївна; Babak, Oleg; Zaichenko, Olga; Zhelezniakova, Natalia; et al. (My University, 2016)
Cough is the most common symptom of respiratory disease. It is caused by stimulation of sensory nerves in themucosa of the pharynx, larynx, trachea and bronchi. Acute sensitisation of the normal cough reflex occurs in a number of conditions, and it is typically induced by changes in air tem-perature or exposure to irritants such as cigarette smoke or perfumes. Results of epidemiologic surveys suggest that patients who seek me-dical care for a cough account for only a small part of the population with this symptom. Chronic cough can be associated with significant distress and impairment in quality of life.
Сучасна практика внутрішньої медицини з невідкладними станами. Ведення хворих з хронічним кашлем
Keywords: trachea and bronchi; сough; respiratory diseases; larynx